Socio-Educational Implications of Creativity from Pedagogical Mediation: A Critical Review [Implicaciones Socioeducativas de la Creatividad a Partir de la Mediación Pedagógica: Una Revisión Crítica] - Poblete-Galvez, C; Toro-Arevalo, S (Universidad Austral de Chile, 2020)
The school continues to be a routine and normative space, notoriously neglecting socio-emotional, cultural, historical, and even political aspects of learning. We believe that the school must integrate educational alternatives that minimize the negative impact of the schooling processes. Thus, creativity emerges as a relevant component of the emotional and cognitive development of the human being. Creativity and its neurobiological bases are presented, describing the close connection it has with learning, presenting behavioral guidelines and pedagogical criteria that would facilitate the promotion of this construct, based on the Experiences of Mediate Learning. Finally, the educational transformation is discussed and stressed, taking the leap from incidental to intentional learning, promoting a pedagogy of the question that enables students to discover the world, beyond the limits and forms defined by the school map. © 2020 Universidad Austral de Chile.